Performance of Variable Negative Stiffness MRE Vibration Isolation System - Run-pu Li; Cheng-bin Du; Fei Guo; Guo-jun Yu; Xiao-guo Lin (Advances in Materials Science and Engineering)
Magnetorheological elastomer (MRE) vibration isolation devices can improve a system’s vibration response via adjustable stiffness and damping under different magnetic fields. Combined with negative stiffness design, these MRE devices can reduce a system’s stiffness and improve the vibration control effect significantly. This paper develops a variable negative stiffness MRE isolation device by combining an improved separable iron core with laminated MREs. The relationship between the negative stiffness and the performance of the device is obtained by mathematical transformation. Its vibration response under simple harmonic excitation at small amplitude and the impact of the volume fraction of soft magnetic particles on the isolation system are also analyzed. The results show that the negative stiffness produced by the magnetic force is a major factor affecting the capacity of the isolation system. Compared to devices of the same size, the isolation system equipped with low-particle volume fraction MREs demonstrates better performance.